2012
DOI: 10.1590/s0103-21002012000900021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of violent TV cartoons watched by school children in Turkey

Abstract: Objective: This study aimed to demonstrate the gender-specific impact of violence-oriented television cartoons on children, and to identify the behaviors demonstrating this influence. Methods: The research was conducted on a total of 300 students chosen by a simple, random method applying a stratified weight in each school. A 20-question instrument was used for data collection, using face-to-face interviews with the students which occurred during visits to primary schools. Results: A significant gender differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
2
7
0
4
Order By: Relevance
“…They also reported that cartoons were effective in attracting and sustaining the attention of the sample studied. Other studies (Ergün, 2012; Ghilzai et al, 2017; Iamurai, 2009) that have examined the effects of cartoons on children also reported that they are effective in behaviour change. The effect of cartoons has also been examined in adults.…”
Section: Literature Reviewmentioning
confidence: 96%
“…They also reported that cartoons were effective in attracting and sustaining the attention of the sample studied. Other studies (Ergün, 2012; Ghilzai et al, 2017; Iamurai, 2009) that have examined the effects of cartoons on children also reported that they are effective in behaviour change. The effect of cartoons has also been examined in adults.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Children might end up picking disparaging language as well as styles of dress, hair and walk and eating habits alongside other traits that exhibit explicit display of negative behaviour from animated cartoons. Ergün (2012) and Nyamai (2013) identified that when programs do not show realistic consequences of animated cartoon violence there is an attendant increase in aggressive behaviour among young viewers. This is because violence is always portrayed as humorous.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Çocukların televizyondan bu açılardan etkilenmelerinin nedeni ise televizyonun çocuklar için eğitici bir araç olmasıdır. Bu eğiticinin programları arasında çocukların en sevdiği program türleri ise çizgi filmlerdir (Ergün, 2012;Koçak, 2016). Hatta günümüzde artık çocuklar çizgi filmleri sadece televizyonlardan değil, tablet bilgisayarlardan ve akıllı telefonlardan izlemektedirler.…”
Section: Introductionunclassified
“…Bu tür olumsuz etkilerinin oluşmasının nedeni ise çocuklara yönelik içeriklerin özellikle çizgi filmlerin içerdiği şiddet oranının yetişkinlere yönelik olan programların içerdiği orandan daha fazla olmasıdır (Wilson vd., 2002). Ayrıca çizgi filmlerdeki öne çıkan karakterler aracılığıyla yapılan olumsuz aktiviteler ödüllendirilmekte ve çekici bir halde çocuklara sunulmaktadır (Coyne ve Whitehead, 2008 Eğlendirici (7,8) 3.47 0.86 Geliştirici (1,2,3,4,5,6) 3.34 0.81 Olumsuz (9,10,11,12,13,14,15,16) 3.01 0.95 Kontrol edici (17,18,19,20,21,22) 2 (Ergün, 2012;Kirsh, 2006…”
Section: Introductionunclassified